Clonal Spread of a Unique Strain of Macrolide-Resistant Mycoplasma Pneumoniae Within a Single Family in Italy. Issue 11 (March 2016) - Chironna, Maria; Loconsole, Daniela; De Robertis, Anna Lisa; Morea, Anna; Scalini, Egidio; Quarto, Michele; Tafuri, Silvio; Germinario, Cinzia; Manzionna, Mariano
Abstract : Abstract: Macrolide-resistant Mycoplasma pneumoniae (MR-MP ) is an increasing problem worldwide. This study describes the clonal spread of a unique strain of MR-MP within a single family. On January 23, 2015, nasopharyngeal swabs and sputum samples were collected from the index case (a 9-year-old girl) in southern Italy. The patient had pneumonia and was initially treated with clarithromycin. MR-MP infection was suspected due to prolonged symptoms despite appropriate antibiotic therapy. Two further cases of pneumonia occurred in relatives (a 7-year-old cousin and the 36-year-old mother of the index case); therefore, respiratory samples were also collected from other family members. Sequence analysis identified mutations associated with resistance to macrolides. Both P1 major adhesion protein typing and multiple loci variable-number tandem repeat analysis (MLVA) typing were performed to assess the relatedness of the strains. The index case, the cousin, the mother, and another 4 family members (twin siblings of the index case, a 3-year-old cousin, and the grandmother) were positive for MR-MP. All strains harbored the mutation A2063G, had the same P1 subtype (1), and were MLVA (7/4/5/7/2) type Z. In addition, the index case's aunt (31 years of age and the probable source of infection) harbored an M pneumoniae strain with the same molecular profile; however, this strain was susceptible to macrolides. This cluster of MR-MP infection/carriage caused by a clonal strain suggests a high transmission rate within this family and highlights the need for increased awareness among clinicians regarding the circulation of MR-MP. Novel strategies for the treatment and prevention of M pneumoniae infections are required.